2001
DOI: 10.1002/1097-4636(200107)56:1<31::aid-jbm1065>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of NDGA-polymerized collagen fibers. I. Evaluation of cytotoxicity with tendon fibroblastsin vitro

Abstract: The material properties of tendon type I collagen fibers polymerized with nordihydroguaiaretic acid (NDGA) are equivalent to native tendon, suggesting that NDGA crosslinking may provide a viable approach to stabilizing collagenous materials for repairing ruptured, lacerated, or surgically transected fibrous tissues, such as tendon and ligament (Koob & Hernandez, Biomaterials, in press). Using standard cytotoxicity tests, the present study evaluated the biocompatibility of these fibers with cultured bovine tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Pure collagen scaffolds, on the other hand, do not possess elastomeric behavior and are generally weak at high porosity without chemical cross-linking (13). Cross-linking of collagen scaffolds is often performed to increase tensile strength and reduce enzymatic lability (18), but common chemical cross-linking techniques can reduce the cytocompatibility of the scaffold (12,14). Earlier reported composites of collagen with polymers involved collagen integration into hydrogel materials (1,4) and combinations with thermoplastic polymers that do not possess the elastic mechanical properties of polyurethanes (6).…”
Section: Discussionmentioning
confidence: 99%
“…Pure collagen scaffolds, on the other hand, do not possess elastomeric behavior and are generally weak at high porosity without chemical cross-linking (13). Cross-linking of collagen scaffolds is often performed to increase tensile strength and reduce enzymatic lability (18), but common chemical cross-linking techniques can reduce the cytocompatibility of the scaffold (12,14). Earlier reported composites of collagen with polymers involved collagen integration into hydrogel materials (1,4) and combinations with thermoplastic polymers that do not possess the elastic mechanical properties of polyurethanes (6).…”
Section: Discussionmentioning
confidence: 99%
“…The only two studies comparing the attachment of cells on two otherwise identical collagen surfaces that were either non-cross-linked or cross-linked were published by Koob et al, 22 who used the nordihydroguaiaretic acid (NDGA) technique, and by Kumar et al, 26 who used chitosan. The observation time points for the assessment of cell attachment were chosen as 24 to 48 h after cell seeding.…”
Section: Cell Attachment Morphology and Orientationmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, it has also been shown that not all cell types show the same affi nity for a given surface. 28 The aim of the GTR procedure is the regeneration of a fully functional periodontium, including new cementum and periodontal ligament (PDL), as well as new bone.…”
Section: Cells Used For In Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations